Canon law of the sacraments for parish ministry - Woestman, William H. 1929- (Ottawa Faculty of Canon Law, St. Paul Univ., 2007)
Smilanic, Daniel: Canon Law has been described as practical ecclesiology, and Fr. Woestman's book is a practical approach to the canon law of sacraments. It is a reliable guide for the parish priest, the deacon or the lay ecclesial minister who has to deal with concrete situations. While he introduces the practitioner to the theology and the legislation, he provides answers to the questions that are asked in parish situations. Although not dealing with concepts that the more technical commentaries would adress, he tackles the concerns that confront those who are involved daily with the traditions of the Church in a particular parish. I recommend this book as an indispensable addition to the basic library of any parish.
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Sacraments (Canon law); Pastoral Theology -- Catholic Church; Pfarrei; Handbuch; Liturgisches Recht; Sakramentenrecht